Methodology and methods of training children with disabilities in an inclusive distance education system - T. M. Egorova; N. N. Belukhina; T. S. Akhmedzyanova (Открытое образование (Москва), 2019)
Purpose of research. Today, one of the main tasks of distance education is a personification of learning, taking into account the mental and physical states of students. Therefore, the purpose of research, conducted by the Institute of Distance and Additional Professional Education of Ulyanovsk State Technical University is to develop a model of a regional distance education system for persons with disabilities based on an inclusive paradigm. One of the model’s components is the organization of training methods, the identification of which was the original purpose of the study, the intermediate result of which is described in the proposed paper.Materials and methods. In order to achieve the purpose of the research, we use a systematic approach, since the inclusive regional distance education system for persons with disabilities is a part of the social system with its structure, characteristics, principles, and laws of development, and a subject-subject approach based on the idea of the individual’s subject activity in his/her life processes.The paper provides a brief retrospective analysis of the distance education development in Russia and abroad. The foreign authors’ works in the field of distance education (D.R. Garrison, B. Holmberg, M. Jeffries, D. Keegan, O. Peters) belong to an earlier period and serve as a starting point for Russian scientists A. Andreev, E. Polat, V.Soldatkin, V. Tikhomirov, S. Shchennikov.A number of well-established classifications of training methods are given and the thesis is suggested that technological innovations lead to a significant expansion of pedagogical methods and techniques, pedagogical innovations that affect the nature of distance education activities for people with disabilities.Results. The result of the first stage of our research work is the propose and description of the author’s methods of organizing the education for children with disabilities: the method of adaptive and expert borrowing, the method of variable and dual training, the method of evolutionary and expert development, and the method of inclusive group virtual learning. These methods expand pedagogicalknowledge. The authors validate feasibility of the possibility of borrowing the benefits of e-learning to study humanities, natural and technical sciences, and propose the tools that allow adapting training to the students’ characteristics, regardless of their physical disabilities. Since the introduction to various fields of activity is difficult for children with disabilities, a dual education system based on the interaction of vocational education institutions and enterprises may provide an opportunity to try themselves in different professions. A virtual company is proposed to be an “employer”.Conclusion. The project deliverable will be a model of an inclusive regional distance education system for children with disabilities, developing and supplementing the theoretical, methodological and technological foundations of e-learning. In the future, a set of conditions for the functioning and development of an inclusive regional distance education system for children with disabilities will be identified, causing the learning process in the system under study. This system is characterized by the use of distance learning technologies with adaptive and expert support of the educational process, borrowing the benefits of e-learning from various areas of knowledge, and defining organizational, technical and pedagogical support for the implementation of the learning process for persons with disabilities.